A New Meet-in-the-Middle Attack on the IDEA Block Cipher - (:unkn) unknown (My University, 2004)
In this paper we introduce a novel meet-in-the-middle attack on the IDEA block cipher. The attack consists of a precomputation and an elimination phase. The attack reduces the number of required plaintexts significantly for 4 and 4.5 rounds, and, to the best of our knowledge, it is the first attack on the 5-round IDEA.